Cemented versus uncemented total knee arthroplasty in younger patients: A protocol of retrospective cohort trial. Issue 18 (May 2020) - Guo, Yuning; Ma, Shufang; Wang, Junbo; Zhang, Qin; Wang, Shaowei; Du, Zhipo
Abstract: Background: Recently, controversy still exists regarding the clinical effects of cemented or cementless technique in young patients in total knee arthroplasty (TKA). In this context, the present study aimed to determine the functional outcomes and clinical reliability of cementless components versus those of conventional cemented components for young patients in primary TKA. Methods: A retrospective review of primary TKAs performed with cementless or cemented fixation between May 2010 and February 2019 was conducted with Institutional Review Board approval. All cases were performed by a single surgeon. Institutional review board approval was obtained prior to conducting chart review and analysis. The primary outcome compared between the 2 fixation groups was the rate of postoperative complications and revision related to TKA, occurring at any point in follow-up. Secondary outcome measures included surgical time, Oxford Knee Score, range of motion, and radiographic outcomes such as progressive radiolucent lines, osteolysis, or component migration. Results: We were able to directly compare the outcomes of cemented versus cementless techniques and might reveal a better technique in TKA. Trial registration: This study protocol was registered in Research Registry (researchregistry5459).